2015
DOI: 10.1007/s12035-015-9151-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke

Abstract: Previous studies had shown that CXC chemokine ligand-12 (CXCL12) plays a significant role in animal models of ischemic stroke, but its role in human stroke is unclear. The aim of this study was to test the relationship between elevated serum circulating CXCL12 levels and the 1-year stroke recurrence in Chinese patients with acute ischemic stroke (AIS). All consecutive patients with first-ever acute ischemic stroke from January 2011 to September 2013 were recruited to participate in the study. Serum levels of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, the role of CXCL12 in patients with AIS had controversies [4,5,9,10]. Gu et al [11] reported that elevated circulating CXCL12 levels at admission are strongly associated with the future recurrence of ischemic stroke in Chinese patients with AIS and Schutt et al [4] found that plasma CXCL12 levels was a predictor of future stroke. In addition, Ruscher et al [12] concluded that immoderate excessive activation of the CXCL12 pathway after stroke contributes to depression of neurologic function after stroke, and Kim et al [13] found that there was a correlation between serum CXCL12 and favorable long-term outcome in patients with AIS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of CXCL12 in patients with AIS had controversies [4,5,9,10]. Gu et al [11] reported that elevated circulating CXCL12 levels at admission are strongly associated with the future recurrence of ischemic stroke in Chinese patients with AIS and Schutt et al [4] found that plasma CXCL12 levels was a predictor of future stroke. In addition, Ruscher et al [12] concluded that immoderate excessive activation of the CXCL12 pathway after stroke contributes to depression of neurologic function after stroke, and Kim et al [13] found that there was a correlation between serum CXCL12 and favorable long-term outcome in patients with AIS.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action for agonists or antagonists may be more related to CXCL12-mediated effects than CXCR7. CXCL12 levels are increased in most pathological conditions that CXCR7 is overexpressed in, including tumors [112,113], rheumatoid arthritis [34,114,115], stroke [116,117], multiple sclerosis [118], traumatic brain injury [119][120][121] and obesity [48]. An exception is that decreased blood levels of CXCL12 are observed in Alzheimer's disease [122].…”
Section: Why Agonists Are Producing Hypothesized Antagonist Resultsmentioning
confidence: 99%
“…First, the elevated hsCRP is likely to be associated with stroke severity (brain tissue lesion size, neurological deficits, etc. ), which itself is associated with prognosis ( 24 , 25 ). This means that hsCRP is likely to be a marker only and is not involved in the mechanism that leads to stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%